GRATIFICACIÓN DIGITAL INSTANTÁNEA Y SU IMPACTO EN EL APRENDIZAJE DE LECTO-ESCRITURA DE LOS ESTUDIANTES DE 8VO AÑO DE EGB DE LA UNIDAD EDUCATIVA MANUEL CÓRDOVA GALARZA 2024 – 2025 - CAMPUZANO MOYA OMAYRA LISBETH (2024)
The objective of this work is to evaluate Instant Digital Gratification and its impact on the learning of Reading and Writing of 8th year EGB students of the Manuel Córdova Galarza Educational Unit 2024 - 2025. In this case, it is a problem that currently affects to countless educational institutions, from which little interest in academic activities is reported, and low performance is very evident. In this regard, it is worth saying that this study focuses on being able to identify and understand how instant digital gratification impacts student learning. It seeks to implement non-digital strategies that can promote the ability to read and write in an appropriate way. and also integrate appropriate and responsible use of technology. The population is made up of students who are studying the different parallels of the 8th year of EGB, from the Manuel Córdova Galarza Educational Unit located in the city of Ventanas, Parroquia 10 de Noviembre; and the sample that was chosen was 25% of the students and 50% of the teachers. In this regard, it should be said that, for sample selection, non-probability Sampling is used, in the case of the Type of Research, the Quantitative Approach was used. According to the level of Research it is Descriptive, according to the sources it is Documentary and the Research Design It is non-experimental. In conclusion, it is considered that the lack of self-regulation in the use of technological devices is one of the most significant effects on students, given that a considerable proportion of students show an inability to limit the use of technological devices, evidencing a lack of self-regulation. which contributes to decreased academic performance and physical and mental health problems.